Harmonization of PPPK Principal Appointment Regulations : Normative Legal Perspective - Candra Husein Puji Putra; Ivan Widjaja; Abdul Rokhim (Asosiasi Penelitian dan Pengajar Ilmu Hukum Indonesia, 2025)
This research aims to analyze the potential legal conflicts arising from the mismatch between the employment contract of Government Employees with Work Agreements (PPPK) and the applicable regulations related to the appointment of school principals. The method used in this research is normative legal research with a statutory approach to examine related regulations. Data collection consists of primary legal materials from laws, secondary materials from legal journals, and tertiary materials as supporting references. The analysis used a qualitative normative method to interpret the data in a comprehensive legal context. The results show significant legal uncertainty regarding the status and rights of PPPK in strategic positions, especially in the school principal position. The inconsistency of regulations regarding tenure and legal protection for PPPKs creates potential conflicts that can affect their career stability and performance. Recommendations regarding legal harmonization and clearer regulations are proposed to ensure legal certainty and protection for PPPKs in strategic positions.